Henry Grey, 3rd Marquis of Dorset, 2nd Duke of Suffolk (c. 1500-1554) : a history in documents - Taylor, James D., 1958- (New York : Algora Publishing, 2015)
"This book aims to provide essentially all the known historical information regarding the man, Henry Grey. He descended from a distinguished and noble heritage that produced two queens, and he gave up a quiet and leisurely life to become one of the most powerful and influential men in England. His influence was so strong, that working in alliance with the Duke of Northumberland, he was able to coerce the young and dying King Edward VI to change the order of succession to the crown, placing his daughter, Lady Jane Grey, on the throne when Edward died"--Provided by publisher.
The Grey ancestry -- Prosperity -- Jane the Queen -- A little rebellion -- Conclusion -- Appendix I: Henry Grey's ancestral tree -- Appendix II: Officers of state during the majority of the period of this book -- Appendix III: Knights elected in the time of King Edward VI; knights of the Garter of King Edward VI; Forty Knights of the Bath of King Edward VI, made on 20 February 1547; Fifty-five Knights of the Carpet, made on 20 February 1547 -- Appendix IV: The "Lane letters"; Lady Laurana's story -- Appendix V: Autographs of some of the main characters in this book -- Appendix VI: A story of Frances Brandon -- Appendix VII: Fifth decade dedication from Henry Bullinger to Henry Grey.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Suffolk, Henry Grey, -- Duke of, -- approximately 1500-1554.; Suffolk, Henry Grey, -- Duke of, -- approximately 1500-1554 -- Family; Northumberland, John Dudley, -- Duke of, -- 1502-1553 -- Friends and associates; Grey, Jane, -- Lady, -- 1537-1554.; Grey, Jane, -- Lady, -- 1537-1554; Northumberland, John Dudley, -- Duke of, -- 1502-1553; Nobility -- England -- Biography; Great Britain -- History -- Edward VI, 1547-1553.; Great Britain -- History -- Edward VI, 1547-1553 -- Sources; Great Britain -- Politics and government -- 1509-1547.; Great Britain -- Politics and government -- 1547-1553.; Grande-Bretagne -- Histoire -- 1547-1553 (Édouard VI); Grande-Bretagne -- Histoire -- 1547-1553 (Édouard VI) -- Sources; Grande-Bretagne -- Politique et gouvernement -- 1509-1547.; Grande-Bretagne -- Politique et gouvernement -- 1547-1553.; BIOGRAPHY & AUTOBIOGRAPHY / Historical; HISTORY / Europe / Great Britain; Families; Friendship; Nobility; Politics and government; England; Great Britain; 1509-1553; Biographies; History; Sources